1995
DOI: 10.1007/bf01795061
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Achilles tendon (tendo calcaneus) with respect to tendon thickness measurements

Abstract: 267 normal controls of different ages underwent achilles tendon thickness measurements by ultrasonography (US) for reference. 96 recruits and 10 young women additionally underwent magnetic resonance imaging of the achilles tendons and calves for more systematic evaluation of the factors influencing tendon thickness. Children under 10 had a tendon thickness (mean +/- SD) of 4.6 +/- 0.8 mm, 10-17 year-olds 6.1 +/- 0.8 mm, 18-30 year-olds 6.3 +/- 0.5 mm and over 30 year-olds 6.9 +/- 1.0 mm. Women had slightly thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
62
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 14 publications
(16 reference statements)
4
62
4
Order By: Relevance
“…20 Our study confirms previous studies by showing that the tendon decreases in antero-posterior diameter and widens at the calcaneal insertion in normal subjects 21 and that there is significant positive correlation between tendon thickness and body height. 22 Compared with a study by Ying et al 13 that was also performed on Chinese subjects, the mean antero-posterior diameter in our study is lower, and the difference shows statistical significance (p 5 0.05). In the study by Ying et al, tendon thickness at the level of the medial malleolus was 5.23 6 0.45 mm.…”
Section: Discussioncontrasting
confidence: 68%
“…20 Our study confirms previous studies by showing that the tendon decreases in antero-posterior diameter and widens at the calcaneal insertion in normal subjects 21 and that there is significant positive correlation between tendon thickness and body height. 22 Compared with a study by Ying et al 13 that was also performed on Chinese subjects, the mean antero-posterior diameter in our study is lower, and the difference shows statistical significance (p 5 0.05). In the study by Ying et al, tendon thickness at the level of the medial malleolus was 5.23 6 0.45 mm.…”
Section: Discussioncontrasting
confidence: 68%
“…Interestingly, it was observed that ethnic factors affected Achilles tendon size, so this study will provide information specific for Turkish population. [2] In this study, we have used ultrasonography for measurements. Magnetic resonance imaging can give more detailed results; [11] but, US imaging has advantages in being non-invasive, cheap, safe (no radiation danger), quick and easily available.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Tendons, as connective tissues, transfer the force produced by muscles to bones. [3] Achilles tendon may carry up to 110 MPa during running, [4] playing a very important role in lower limb biomechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Harris & Peduto in their studies, intended to create an archive by radiologically imaging the normal and diseased achilles tendons. Additionally, in a number of conducted studies, the researchers aimed at finding the thickness of achilles and patella tendons through the ultrasonographic method (Fredberg et al, 2008;Kallinen & Suominen, 1994;Koivunen-Niemelä & Parkkola, 1995). Chao et al (1997) researched into the termination positions of the achilles tendons anatomically in fresh cadavers.…”
Section: Introductionmentioning
confidence: 99%